Risk Factors for Open-angle Glaucoma in Persons of Latin American Descent. Issue 3 (March 2020) - Wurster, Patrick; Harris, Alon; Gonzalez, Andrea C.; Adjei, Susuana; Verticchio Vercellin, Alice; Mathew, Sunu; Lang, Matt; Eikenberry, Jennifer; Siesky, Brent
Abstract : Purpose: The aim of this paper is to concisely summarize what is currently known about OAG among persons of LAD in the United States for the purpose of improving individualized care and highlighting areas requiring further study. Materials and Methods: Review of relevant literature was performed through PubMed and Google Scholar from October 1978 through November 11, 2019. Results: As the Latin American population grows within the United States, it is predicted that by 2050, men of LAD will make up the largest demographic group with OAG. Persons of LAD experience a greater increase in OAG prevalence per decade of life compared with persons of African descent and may have unique risk factors. In particular, those with African ancestry and hypertension are at greater risk of elevated intraocular pressure (IOP). Maximum IOP, variability in IOP, and diabetes are also important considerations. Unique anatomic and physiological characteristics such as scleral tensile strain, longer axial length, thin corneas, and corneal hysteresis may play a role in this population's unique risk for the development and progression of OAG. Conclusions: OAG represents a growing concern among persons of LAD in the United States; however, information on specific risk factors in this population currently remains limited. Studies should be designed to investigate the LAD population and their respective structural, vascular, and social risk factors for the development and progression of OAG to assist clinicians in improving outcomes for this growing population.